Crepidotus lutescens sp. nov. (Inocybaceae, Agaricales), an ochraceous salmon colored species from northeast of China - Ge, Yupeng; Yang, Sisi; Bau, Tolgor (Phytotaxa, 2017)
Crepidotus lutescens is described as new from Chang bai Mountain, Jilin Province, China. This species is distinctive due to its ochraceous salmon pileus, clamped hyphae, subglobose to broadly ellipsoid basidiospores with a granular to warty ornamentation, and lageniform cheilocystidia with capitate apices. Illustrations, photographs of basidiocarps, and microscopic features of this species are provided in this paper. Based on morphological study, this species is unique compared to existing Crepidotus species. Phylogenetic analyses based on ITS sequences with Maximum Likelihood (ML) and Bayesian Analysis (BA) also showed that C. lutescens was clearly independent from related species.